Stabilizing high-order discrete dynamical systems by a lagged adaptive adjustment mechanism - Wiehong Huang (Discrete Dynamics in Nature and Society)
A lagged adaptive adjustment mechanism has been developed to stabilize a high-order discrete system. Theoretical proofs and computer simulations have been provided to show the effectiveness and efficiency of this new mechanism in practice. The mechanism ensures that the adjusted system converges to its generic fixed points and achieves the convergence with a high speed. Besides, it requires neither a priori information about the system itself nor any external generated control signal.